Manajemen Pencegahan Serangan Jaringan Wireless Dari Serangan Man In The Middle Attack - Tengku Mohd Diansyah; Ilham Faisal; Dodi Siregar (Kesatria : Jurnal Penerapan Sistem Informasi (Komputer dan Manajemen), 2023)
Currently, wireless networks are very widely used to communicate because wireless networks are very fast and communicate without using cables, by using this wireless it turns out that there are weaknesses or security gaps due to irresponsible people illegally such as looking for backdoor gaps to infiltrate and attack aspects of authenticity. If a crime occurs, how to prevent the crime or attack. In this article, the possibility of an attack with the type of attack carried out is a man in the middle attack from this attack experiment will be carried out 5 times the attack experiment in this experiment the calculation of QoS (Quality of Service) is carried out, namely calculating how much packet loss and the results obtained in this attack experiment with the calculation of packet loss as much as 0.291% loss, attack 1 model 2 with packet loss 0.173%, attack 2 model 2 with packet loss which means this attack successfully attacks wireless communication. To prevent this attack activity, first know the technique of how the attack runs on a wireless network, using ettercap on linux times.